Liquid-liquid and solid-liquid extractors - Duroudier, Jean-Paul (ISTE Press, Ltd ; Elsevier Ltd., 2016)
Liquid-Liquid and Solid-Liquid Extractors, part of the Industrial Equipment for Chemical Engineering set, presents a concise and easy-to-use book on the calculation of differential liquid-liquid extraction, an investigation of equilibrium and material transfer between a fluid and a divided solid, and the fundamentals of liquid-solid extraction, among other strategies. The author also provides methods needed for the understanding the machinery used in applied thermodynamics in the hopes of encouraging students and engineers to construct the programs they need. Chapters are complemented with appendices which provide additional information and associated references.
Keywords: Extraction (Chemistry); elektronické knihy; electronic books